Habla Español? The Growing Number of Spanish Speaking Nordic Americans - Roinila, Mika (Migration-Muuttoliike, 2010)
Scholars have most often concentrated on the retention and upkeep of native languages along with the trend in assimilation to American society and the dominant English language. Seldom have we studied other languages that are spoken and maintained by the immigrant communities. This paper examines new data available through the Minnesota Population Center and the newly developed Integrated Public Use Microdata Series (IPUMS) data base. By analyzing past and current U.S. Census data, distinct trends in languages spoken at home are encountered helping us project changes to come in years ahead. Questions of dominant languages across the United States reveal that Spanish speaking Nordic Americans are increasing at high rates. Regional clustering of Spanish speakers and surprising fi ndings as to the rank of each national language within each ethnic group are investigated. These fi ndings are signifi cant in helping us gain a better understanding of the changing linguistic practices of each Nordic group.
Keywords: IPUMS; Spanish language; Nordic Americans